2009
DOI: 10.1108/14777260910983970
|View full text |Cite
|
Sign up to set email alerts
|

Micro data assessment of Russian drug benefit monetization

Abstract: The paper represents an attempt to use a large sample statistical analysis along with the Federal Social Insurance Fund data in order to assess drug benefit groups of behavior in Russian regions before and after the drug benefit reform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Thirty‐eight articles were obtained from the database searches. Based on a preliminary review of the abstracts, 18 articles were excluded because they were not original economic analyses [17–34] . The remaining 20 articles were then located and the full articles were evaluated to determine if they met the study criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐eight articles were obtained from the database searches. Based on a preliminary review of the abstracts, 18 articles were excluded because they were not original economic analyses [17–34] . The remaining 20 articles were then located and the full articles were evaluated to determine if they met the study criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a preliminary review of the abstracts, 18 articles were excluded because they were not original economic analyses. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The remaining 20 articles were then located and the full articles were evaluated to determine if they met the study criteria. After reviewing the full articles, one article was excluded because it was not on Russia [35] and three were excluded because they were not original economic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The standard solution to the adverse selection problem is to recommend a mandatory insurance scheme (Pauly and Zeng 2004), but in Russia and other emerging economies the feasibility and popularity of this solution is low. Indeed, Russia's program of social welfare monetization in 2005 represents a salutary lesson in this regard (Besstremyannaya 2009). Second, while the evidence is relatively weak, the data does suggest that more affluent residents of the country are against joining voluntary drug insurance schemes for reasons which may reflect their existing private insurance or simply their confidence concerning the affordability of treatment in the event of illness.…”
Section: Discussion and Policy Recommendationsmentioning
confidence: 95%
“…employees of civil and armed services or those moving to strategically important or remote areas), but not based on income. As such, privileges were neither designed to serve as social assistance or relieve hardships, nor were they exclusively awarded to low-income consumers (Struyk et al, 2007;Wengle & Rasell 2008;Besstremyannaya, 2009b).…”
Section: The 2005 Social Benefits Reform In the Russian Federationmentioning
confidence: 99%
“…The changes brought by the reform affected millions of Russian beneficiaries, yet studies that evaluate and track effects of the reform during the extended post-reform period are still lacking. The studies that were conducted during the post-reform period mainly assessed the general design and reform implementation (Besstremyannaya, 2009b;Ovcharova, 2005;Volchkova et al, 2006;Alexandrova & Struyk, 2007;Sinitsina, 2009;Wengle & Rasell, 2008); reported on short-term adjustments that have arisen from the reform and its public perception (Besstremyannaya, 2009b;Hahulina, 2005;Alexandrova & Struyk, 2007;Struyk et al, 2007;Wengle & Rasell, 2008;Parfitt, 2007;Zasimova, 2010); and gave numerical estimations of benefit groups' behavior before and after the reform (Besstremyannaya, 2009b).…”
Section: Introductionmentioning
confidence: 99%